Đáp án:
$A=1$
Giải thích các bước giải:
Đặt $A = \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - {x^8} + {y^8} + 1$
Ta có:
$\begin{array}{l}
A = \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - {x^8} + {y^8} + 1\\
= \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - \left( {{{\left( {{x^4}} \right)}^2} - {{\left( {{y^4}} \right)}^2}} \right) + 1\\
= \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - \left( {{x^4} - {y^4}} \right)\left( {{x^4} + {y^4}} \right) + 1\\
= \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - \left( {{x^2} - {y^2}} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) + 1\\
= \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - \left( {x - y} \right)\left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) + 1\\
= \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) - \left( {x + y} \right)\left( {{x^2} + {y^2}} \right)\left( {{x^4} + {y^4}} \right) + 1\\
\left( {do:x - y = 1} \right)\\
= 0 + 1\\
= 1
\end{array}$